Teknologi Perlu Hati Nurani: Jalan Indonesia Menuju Inovasi Etis dan Berkelanjutan - Wicaksono, Mitchel Wahyu; Asbari, Masduki; Fahriza, Siti Dede (Journal of Information Systems and Management (JISMA), 2025)
The purpose of this study is to spark discussion on how education and technology can be used as tools to create more aware and visionary citizens, who will ultimately shape a better future for Indonesia. This study report uses a descriptive qualitative method by conducting observations because the data sources were obtained by listening to the narration from Gita Wirjawan's YouTube channel entitled Alamanda Shantika: Technology Needs Conscience | Endgame #17. The results of this study explain that rapid technological advances must be balanced with increased human awareness and intelligent conscience. Technology should function as a tool to encourage humans to recognize themselves and react positively to the world, not the other way around.